2015
DOI: 10.1159/000430343
|View full text |Cite
|
Sign up to set email alerts
|

The Adipokine Chemerin Induces Apoptosis in Cardiomyocytes

Abstract: Background: The adipokine chemerin has been associated with cardiovascular disease. We investigated the effects of chemerin on viability and intracellular signalling in murine cardiomyocytes, and the effects of insulin and TNF-α on cardiomyocyte chemerin production. Methods: Hoechst dye vital staining and cell cycle analysis were used to analyse the viability of murine cardiac cells in culture. Western blot was used to explore the phosphorylation of AKT and caspase-9 activity in neonatal rat cardiomyocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 82 publications
2
37
0
3
Order By: Relevance
“…Furthermore, chemerin was able to induce functional angiogenesis in these cells . In contrast, other examinations have indicated opposite effects by demonstrating that chemerin promotes apoptosis in human endothelial and vascular smooth muscle cells and murine cardiomyocytes . We assume that chemerin plays a crucial role in the pathophysiology of cardiovascular diseases, but further research is needed addressing the complex underlying mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, chemerin was able to induce functional angiogenesis in these cells . In contrast, other examinations have indicated opposite effects by demonstrating that chemerin promotes apoptosis in human endothelial and vascular smooth muscle cells and murine cardiomyocytes . We assume that chemerin plays a crucial role in the pathophysiology of cardiovascular diseases, but further research is needed addressing the complex underlying mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…There is a lack of data concerning the influence of chemerin on apoptosis. Rodríguez-Penas et al [51] reported that chemerin induces apoptosis, reduces AKT phosphorylation, and increases caspase-9 cleavage in murine cardiomyocytes, suggesting that chemerin plays a role in the physiopathology of cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, chemerin was reported to be a key regulator of cardiovascular disease, including hypertension, coronary atherosclerosis disease, and myocardial infarction (Kadoglou et al, 2015). In patients with type 2 diabetes, elevated serum levels of chemerin have been associated with heart failure (Zhou et al, 2019) while chemerin was shown to induce murine cardiomyocyte apoptosis through inflammatory processes (Rodriguez-Penas et al, 2015). These results suggest that chemerin plays an important role in DCM by inducing cardiac inflammation.…”
Section: Introductionmentioning
confidence: 99%